2005
DOI: 10.1111/j.1365-2036.2005.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron and insulin resistance

Abstract: SUMMARYBackground: Preliminary clinical and experimental results suggest that iron can modify hepatocytes' insulin sensitivity by interfering with insulin receptor and intracellular insulin signalling. Aim: To evaluate in vivo the influence of iron on insulin resistance and insulin release in patients with nonalcoholic fatty liver disease and in vitro the interaction between iron and insulin sensitivity by analysing the effect of iron manipulation on insulin receptor expression in hepatoblastoma HepG2 cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 8 publications
1
66
1
1
Order By: Relevance
“…However, recent reports showed that iron status influences insulin signaling and glucose uptake in the liver 27 and adipose tissue. 28 Iron overloading decreased insulin signaling evaluated by the phospho-Akt/Akt ratio and up-regulated adipokines favoring insulin resistance such as resistin, 28 which can explain the independent association between ferritin level and insulin resistance in our study.…”
Section: The Association Between Insulin Resistance and Serum Ferritimentioning
confidence: 99%
“…However, recent reports showed that iron status influences insulin signaling and glucose uptake in the liver 27 and adipose tissue. 28 Iron overloading decreased insulin signaling evaluated by the phospho-Akt/Akt ratio and up-regulated adipokines favoring insulin resistance such as resistin, 28 which can explain the independent association between ferritin level and insulin resistance in our study.…”
Section: The Association Between Insulin Resistance and Serum Ferritimentioning
confidence: 99%
“…Facchini et al [110] have shown improvement in liver enzyme levels in 17 NAFLD patients with impaired glucose tolerance undergoing serial phlebotomy. According to Fargion et al [111], in 42 NAFLD patients, serum transaminase levels were significantly decreased after a 4-month hypocaloric diet, and a further reduction was observed after phlebotomies. Sumida et al [112] also reported that phlebotomy decreased serum transaminase activities in Japanese patients with biopsy-proven NASH.…”
Section: Metformin Cq: Are Biguanides Effective For Patients With Nafmentioning
confidence: 99%
“…At present, treatment strategies for NAFLD are involved in prevention by modifying risk-factors of the disease, such as calorie restriction and physical exercise. The in vitro investigation of iron chelators has shown that the addition of chelator improves the insulin resistance of hepatocytes [49]. While the in vitro data look promising, the effect of iron removal on insulin resistance in vivo needs to be validated prospectively in NAFLD patients with documented hepatic iron excess.…”
Section: Non-alcoholic Fatty Liver Disease and Metabolic Syndromementioning
confidence: 99%